Self-Efficacy dan Stres Psikologis Pada Penderita Kanker Payudara: Studi Analitik di RSUD Waled Kabupaten Cirebon - Endah Sari P; Muadi Muadi; Ani Nurhaeni; Dewi Erna Marisa; Thia Oktiany; Rosalia Rahayu; Lili Wahyuni (Universitas Malahayati Lampung, 2025)
ABSTRACT Self efficacy is a person’s belief in his ability to regulate himself, and take action to achieve certain skills. Stress is the body’s response caused by demands from outside the individual that exceed the ability to solve problems. This study aims to determine the relationship between self efficacy and stress levels in breast cancer patients at Waled Hospital, Cirebon Regency. This type of research is quantitative with cross-sectional approach. Sampling using purposive sampling technique amounted to 31 respondents. The instrument used were standard self efficacay questionnaires and DASS 42 (Depression, Anxiety and Stres). Data analysis using chi-square. The research location was at Waled Hospital, Cirebon Regency. The results of the study found that most of the respondents experienced less self efficacy with moderate stress levels dominating. 31 respondents experienced less self efficacy (35,5%) and some respondents with moderate stress levels (41,9%). The results of the chi-square test obtained a p-value of 0.000 a=0.05, so H0=rejected, which means that there is a relationship between self efficacy and the stress levels of breast cancer patients at Waled General Hospital. For breast cancer patients who have low self efficacy, it is recommended to add more insight and knowledge so that their self efficacy increases so that stress levels are also reduced in patients at Waled Hospital, Cirebon Regency. Keywords: Breast Cancer, Self Efficacy, Stress Levels ABSTRAK Self Efficacy merupakan keyakinan sesorang terhadap kemampuannya untuk mengatur diri sendiri,dan mengambil tindakan untuk mencapai keterampilan tertentu. Stress adalah respon tubuh yang diakibatkan karena adanya tuntutan dari luar diri individu yang melebihi kemampuan dalam menyelesaikan masalah. Penelitian ini bertujuan untuk mengetahui hubungan self efficacy dengan tingkat stress pada pasien kanker payudara di RSUD Waled Kabupaten Cirebon. Jenis penelitian ini adalah kuantitatif dengan pendekatan cros sectional. Pengambilan sampel menggunakan Teknik purposive sampling berjumlah 31 responden. Instrumen yang digunakan berupa kuesioner baku Self-Efficcay dan DASS 42 (Depression, Anxiety and Stres). Analisa data menggunakan Chi-Square. Tempat penelitian di RSUD Waled Kabupaten Cirebon. Hasil penelitian didapatkan Sebagian besar responden mengalami Self Efficcay kurang dengan di dominasi tingkat stress sedang. 31 responden mengalami self efficacy kurang sebanyak (35,5%) dan Sebagian responden dengan tingkat stress sedang sebanyak (41,9%). Hasil uji chi-square didapatkan p-value 0,000 a=0,05 maka H0=ditolak yang artinya ada hubungan antara self efficacy dengan tingkat stress pasien kanker payudara di RSUD Waled Kabupaten Cirebon. Bagi pasien kanker payudara yang memiliki Self Efficcay rendah disarankan agar menambah wawasan dan ilmu yang lebih banyak agar self efficacy nya meningkat sehingga tingkat stress juga berkurang pada pasien di RSUD Waled Kabupaten Cirebon. Kata Kunci: Efikasi Diri, Tingkat Stres, Kanker Payudara.